2023
DOI: 10.3389/fimmu.2023.1206953
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral blood CD3+HLADR+ cells and associated gut microbiome species predict response and overall survival to immune checkpoint blockade

Joao Gorgulho,
Christoph Roderburg,
Fabian Beier
et al.

Abstract: BackgroundThe search for biomarkers to identify ideal candidates for immune checkpoint inhibitor (ICI) therapy is fundamental. In this study, we analyze peripheral blood CD3+HLADR+ cells (activated T-cells) as a novel biomarker for ICI therapy and how its association to certain gut microbiome species can indicate individual treatment outcomes.MethodsFlow cytometry analysis of peripheral mononuclear blood cells (PBMCs) was performed on n=70 patients undergoing ICI therapy for solid malignancies to quantify HLA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 54 publications
1
0
0
Order By: Relevance
“…It indicates the restoration of the body’s immune system following PD-1/PD-L1 treatment, leading to the reconstruction of anti-tumor immunity [ 24 ]. The previous studies indicated that, in lung cancer [ 25 ] and renal cell carcinoma [ 26 ] patients receiving ICI therapy, CD8 + T cells with effector-like phenotypes (HLA-DR+, CD38+) proliferated, while HLA-DR + CD3 + T cells increase after ICI therapy across various types of tumors [ 27 ], aligning with our results. Tumor biomarkers, including CEA, SCC, Cyfra 21 − 1, and NSE, serve as crucial indicators in predicting treatment response in lung cancer patients undergoing ICI therapy [ 28 30 ].…”
Section: Discussionsupporting
confidence: 91%
“…It indicates the restoration of the body’s immune system following PD-1/PD-L1 treatment, leading to the reconstruction of anti-tumor immunity [ 24 ]. The previous studies indicated that, in lung cancer [ 25 ] and renal cell carcinoma [ 26 ] patients receiving ICI therapy, CD8 + T cells with effector-like phenotypes (HLA-DR+, CD38+) proliferated, while HLA-DR + CD3 + T cells increase after ICI therapy across various types of tumors [ 27 ], aligning with our results. Tumor biomarkers, including CEA, SCC, Cyfra 21 − 1, and NSE, serve as crucial indicators in predicting treatment response in lung cancer patients undergoing ICI therapy [ 28 30 ].…”
Section: Discussionsupporting
confidence: 91%